Molecular biology of human pathogenic viruses - Ryu,Wang-Shick (Elsevier, 2017)
Molecular Virology of Human Pathogenic Viruses presents robust coverage of the key principles of molecular virology while emphasizing virus family structure and providing key context points for topical advances in the field. The book is organized in a logical manner to aid in student discoverability and comprehension and is based on the author's more than 20 years of teaching experience. Each chapter describes the viral life cycle covering the order of classification, virion and genome structure, viral proteins, viral genome replication, and the effect on host and an emphasis on virus-host interaction is conveyed throughout the text.